Level Shifted Discontinuous PWM Algorithms to Minimize Common Mode Voltage for Cascaded Multilevel Inverter Fed Induction Motor Drive - M. Nayeemuddin; T. Bramhananda Reddy; M. Vijaya Kumar (Institute of Advanced Engineering and Science, 2018)
This paper presents combinations of level shifted pulse-width modulation algorithm with conventional discontinuous pulse-width modulation methods for cascaded multilevel inverters. In the proposed DPWM a zero sequence signal is injected in sinusoidal reference signal to generate various modulators with easier implementation. The analysis four various control strategies namely Common Carrier (CC), Inverted Carrier (IC), Phase Shifted (PS) and Inverted Phase Shift (IPS) for cascaded multilevel inverter fed induction motor drive has been illustrated. To validate the proposed work experimental tests has been carried out using dSPACE controller. Experimental study proves that using proposed algorithms reduction in common-mode voltage with fewer harmonics along with reduced switching loss for a cascaded multilevel inverter fed motor drive has been achieved.